EXOSOME RELEASE AND CARGO IN DOWN SYNDROME - Hamlett, Eric D. (Dev Neurobiol, 2019)
Down syndrome (DS) is a multisystem disorder affecting one in 800 births worldwide. Advancing technology, medical treatment, and social intervention have dramatically increased life expectancy, yet there are many etiologies of this disorder that are in need of further research. The advent of the ability to capture extracellular vesicles (EVs) in blood from specific cell types allows for the investigation of novel intracellular processes. Exosomes are one type of EVs that have demonstrated great potential in uncovering new biomarkers of neurodegeneration and disease, and also that appear to be intricately involved in the transsynaptic spread of pathogenic factors underlying Alzheimer’s disease (AD) and other neurological diseases. Exosomes are nanosized vesicles, generated in endosomal multivesicular bodies (MVBs) and secreted by most cells in the body. Since exosomes are important mediators of intercellular communication and genetic exchange, they have emerged as a major research focus and have revealed novel biological sequelae involved in conditions afflicting the DS population. This review summarizes current knowledge on exosome biology in individuals with DS, both early in life and in aging individuals. Collectively these studies have demonstrated that complex multicellular processes underlying DS etiologies may include abnormal formation and secretion of extracellular vesicles such as exosomes.